The Effect of Sodium Butyrate and Sodium Propionate on Breast Cancer Cell Migration and Epithelial-to-Mesenchymal Transition (EMT) - Kharazi, Dania (2023)
Short-chain fatty acids (SCFAs), mainly sodium butyrate (NaB) and sodium propionate (NaP), have recently garnered attention for their potential roles in modulating tumor behavior. While their effect has been well-defined in colorectal cancer, their therapeutic potential and the underlying mechanisms involved remain elusive in breast cancer. This study aims to investigate the anti-tumor effects of NaB and NaP in two distinct breast cancer cell lines, the luminal epithelial-like MCF-7 and the triple-negative mesenchymal-like MDA-MB-231. The cytotoxic effect of NaB and NaP on cell proliferation and 3D spheroid generation was evaluated using MTT and hanging drop assays. The anti-migratory potential of both drugs was investigated through transwell migration and wound healing assays. Moreover, their role in regulating epithelial-to-mesenchymal transition (EMT) was examined by assessing expression levels of Ecadherin, vimentin, and β-catenin in untreated versus treated cells through RT-qPCR and western blot analyses. Our results noted a dose-dependent and time-dependent inhibition of cellular proliferation and an impairment of spheroid formation in both cell lines, with NaB exerting a more potent effect than NaP. The migration assays showed that both SCFAs can significantly inhibit migration in MDA-MB-231 but not MCF-7 cells following 24h of treatment. Finally, treatment with NaB or NaP altered the mRNA and protein profile of EMT-associated markers, suggesting a potential reversal of the EMT process and a possible mechanism mediating the antitumor effects of the drugs. In conclusion, our study highlights the promising therapeutic potential of NaB and NaP, providing insight into their inhibitory effects on cell proliferation and migration as well as their potent EMT regulatory role in breast cancer.